Food Ingredient Storage Procedures in the Kitchen of Shante Hotel Xitou Taiwan - Jerudin, Yohanes; Rai Antara, I Made Agung; Rusmiati, Ni Nyoman (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2026)
Food storage is a critical control activity in hotel kitchen operations because it determines raw material quality, hygiene, stock rotation, and food safety before production. This study aimed to analyze food storage procedures, identify operational constraints, and describe corrective efforts implemented by kitchen staff at Shante Hotel Xitou Taiwan. The study used a descriptive qualitative method. Primary data were obtained through direct observation and interviews with the hotel manager and kitchen staff, while secondary data were obtained from hotel documents and relevant literature. The results show that food storage procedures generally followed hotel food safety principles, including supplier-based receiving checks, physical quality and expiry-date inspection, grouping of ingredients into dry storage, chiller, and freezer areas, use of food containers, and implementation of the First In, First Out (FIFO) system. However, field observation found several nonconformities, particularly suboptimal chiller and freezer temperatures due to ageing equipment, limited storage capacity, incomplete labeling on several food containers, and inconsistent staff discipline during busy operational periods. Corrective actions included rearranging storage space, increasing the use of food containers, strengthening FIFO through front-placement of older items, improving labeling practice, and maintaining routine sanitation. The study concludes that the procedure is generally appropriate but requires stronger temperature monitoring, labeling discipline, storage capacity control, and periodic internal supervision to ensure consistent food safety in hotel kitchen operations.